2013
DOI: 10.1104/pp.112.208736
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of Type-B Response Regulators in the Arabidopsis Cytokinin Response    

Abstract: Cytokinins play critical roles in plant growth and development, with the transcriptional response to cytokinin being mediated by the type-B response regulators. In Arabidopsis (Arabidopsis thaliana), type-B response regulators (ARABIDOPSIS RESPONSE REGULATORS [ARRs]) form three subfamilies based on phylogenic analysis, with subfamily 1 having seven members and subfamilies 2 and 3 each having two members. Cytokinin responses are predominantly mediated by subfamily 1 members, with cytokinin-mediated effects on r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
72
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 66 publications
7
72
0
Order By: Relevance
“…ARR1-, ARR10-, and ARR12-Regulated WUS Expression Plays Critical Roles in Shoot Regeneration Double and triple mutants of ARR1, ARR10, and ARR12 could not generate shoots under in vitro culture owing to cytokinin insensitivity (Hill et al, 2013;Ishida et al, 2008). Here, we used ethanol-induced artificial microRNAs to silence the transcription of ARR1, ARR10, and ARR12 at different stages of shoot formation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…ARR1-, ARR10-, and ARR12-Regulated WUS Expression Plays Critical Roles in Shoot Regeneration Double and triple mutants of ARR1, ARR10, and ARR12 could not generate shoots under in vitro culture owing to cytokinin insensitivity (Hill et al, 2013;Ishida et al, 2008). Here, we used ethanol-induced artificial microRNAs to silence the transcription of ARR1, ARR10, and ARR12 at different stages of shoot formation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that shoot regeneration capacity was impaired in the arr1 single mutant, as well as its double and triple mutants with arr10 and arr12, indicating that type-B ARRs, which are key regulators in cytokinin signaling, are required for shoot regeneration in Arabidopsis (Ishida et al, 2008;Hill et al, 2013). To determine the roles of ARR in the regeneration of shoots in callus on SIM, the transcription of ARR1, ARR10, and ARR12 needs to be temporally repressed.…”
Section: Reestablishment Of Shoot Meristem Requires the Function Of Amentioning
confidence: 99%
See 2 more Smart Citations
“…We tested this hypothesis by examining the ethylene control of RAM size in type B arr mutants (Table I), focusing on LOF mutations of ARR1, ARR2, ARR10, and ARR12, which are the principle type B ARRs expressed in the root (Mason et al, 2004;Hill et al, 2013). We initially examined the triple mutants arr1-3 arr10-2 arr12-1 and arr2-2 arr10-2 arr12-1 (Mason et al, 2005), examining their responsiveness to 1 and 10 mL L 21 ethylene (Fig.…”
Section: Role Of His Kinase Activity Of the Ethylene Receptors In Conmentioning
confidence: 99%